A Giant Renal Vein Aneurysm in a Patient with Liver Cirrhosis. (6th September 2016) - Filis, Konstantinos; Galyfos, George; Ketikoglou, Ioannis
Abstract : We present an unusual case of a 40-year-old female patient with liver cirrhosis and diffuse abdominal pain. The imaging studies revealed a huge renal vein aneurysm. The patient refused any interventional management, despite the risk of possible rupture, and after a week of mild pain therapy, she was discharged. She was followed up closely, and after one year, she remains asymptomatic. Conservative management of such patients has been described before with success. However, open repair or percutaneous thrombosis of the aneurysm remains the indicated therapy, when vein patency is an issue for organ viability.